A case of tongue swelling after S-1, oxaliplatin, and trastuzumab for HER2-positive gastric cancer - Taichi Abe; Tatsuya Sumiya; Ayaka Tsuji; Izumi Hanai; Yukiko Otomo; Takae Yamamoto; Emiko Iguchi (Bulletin of the National Research Centre, 2023)
Abstract Background We report a case of a patient with HER2-positive gastric cancer with marked tongue swelling during the second cycle of S-1, oxaliplatin, and trastuzumab. Case presentation The patient was a 74-year-old male, who was taking an angiotensin II receptor blocker (ARB) for pre-existing hypertension, with no history of allergies, diagnosed with HER2-positive gastric cancer, treated with tegafur, gimeracil, and oteracil potassium (S-1) and oxaliplatin for the first cycle, and trastuzumab was added from the second cycle. Three weeks after initiation, during an outpatient visit, grade 2 oral mucositis and significant enlargement of the patient's tongue were observed. Due to the risk of airway obstruction, the patient was referred to an otolaryngologist. After examination, hereditary angioedema was ruled out, and treatment was discontinued in view of ARB-induced angioedema. However, the tongue swelling did not improve markedly. Considering disease progression due to the discontinuation of chemotherapy, it was decided to change S-1 to capecitabine and continue treatment, and chemotherapy was resumed. Conclusions Angioedema has been reported to be hereditary and drug-related, and angiotensin-converting enzyme (ACE) inhibitors and ARBs have also been reported to lead to drug-related adverse events. Since the patient had oral mucositis at the time of onset and was taking an ARB, it is thought that oxaliplatin and S-1(SOX), and trastuzumab during ARB therapy induced oral mucositis, leading to the development of angioedema.